(untitled) (American Journal of Pedagogical and Educational Research, 2023)
In this article, in the privatization of non-agricultural land plots, auctions, Internet auctions, e-commerce platform, implementation of entrepreneurship and urban development activities, Evaluation activities, Categories of land plots to be privatized, vacant land plots, agricultural lands owned by local government bodies, problems of state real estate objects are revealed.